Gender Matters Race, Class and Sexuality in the Nineteenth-Century South - Whites, L.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2005)
What role did gender play in the secession crisis? In the loyalty of the civilian population during the Civil War? In the formation of the Ku Klux Klan? In class organization and conflict in the postwar textile industry? Why was the first woman senator from the U.S. South? What role did sexuality and gender play in the explosion of racial violence in the late nineteenth century? These questions and many others concerning the critical role that gender played in the major events of the nineteenth-century South and the nation more generally are addressed in this collection of essays.
Keywords: United States—History.; History, Modern; Sociology; America—History.; US History; Modern History; Gender Studies; History of the Americas